PERBANDINGAN PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN MODEL PEMBELAJARAN LANGSUNG TERHADAP HASIL BELAJAR SISWA - Agusman Agusman; Sitti Mania; Fitriani Nur; Andi Dian Angriani (Universitas Muhammadiyah Makassar, 2021)
This study aims to find out if the application of PBL learning model is effective to students' math learning results, which involved 40 students at SMAN 17 Gowa in Gowa district. This type of research is Quasi Experimental Design with Nonequivalent Control Group Design design. The research instruments used are tests, analyzed using descriptive statistics and inferential statistics with t-tests. The results of this study showed that there are differences in average math learning outcomes of students who do not use the learning model and who use the PBL model. Implementation of PBL learning model effectively on students' math learning outcomes.